2021
DOI: 10.1186/s40001-021-00517-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic factors of intensive and non-intensive 1014 COVID-19 patients: an experience cohort from Alahsa, Saudi Arabia

Abstract: Background COVID-19 is a worldwide pandemic and has placed significant demand for acute and critical care services on hospitals in many countries. Objectives To determine the predictors of severe COVID-19 disease requiring admission to an ICU by comparing patients who were ICU admitted to non-ICU groups. Methods A cohort study was conducted for the laboratory-confirmed COVID-19 patients who were admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 64 publications
7
22
1
Order By: Relevance
“…Fatigue, a sore throat, muscle ache, a headache and chest pain were found to be less common and abdominal pain, a loss of smell and a loss of taste were the least common presenting complaints. This finding is similar to previous studies; however, the lower rates of the loss of smell and taste have been previously suggested to be a result of underreporting and neglect by those who suffer from a severe infection [ 14 , 15 , 16 , 17 , 18 ]. Our study used multiple logistic regression and discovered that age, nationality and ethnicity, the duration of mechanical ventilation, SOFA score and the presence of IHD were significant predictors of the survival rate.…”
Section: Discussionsupporting
confidence: 92%
“…Fatigue, a sore throat, muscle ache, a headache and chest pain were found to be less common and abdominal pain, a loss of smell and a loss of taste were the least common presenting complaints. This finding is similar to previous studies; however, the lower rates of the loss of smell and taste have been previously suggested to be a result of underreporting and neglect by those who suffer from a severe infection [ 14 , 15 , 16 , 17 , 18 ]. Our study used multiple logistic regression and discovered that age, nationality and ethnicity, the duration of mechanical ventilation, SOFA score and the presence of IHD were significant predictors of the survival rate.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the included studies comprised only admitted patients, which may skew the findings and should not be generalized to all SARS-COV-2 patients. Non-admitted COVID-19 patients were not represented in these studies and thus the exact prevalence of coinfections could not be calculated for all SARS-CoV-2 infected patients [ 83 , 84 , 85 ]. The findings in this meta-analysis showed different results from previous systematic meta-analyses that evaluated coinfections among COVID-19 patients [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing age in combination with male gender and BMI ≥ 30 might denote seriously sick patients who can potentially have more morbidity and propensity to die. The majority of patients hospitalized with SARS-CoV-2 are older and seemed to have underlying medical conditions [ 97 , 98 ], with increased age being associated with clinical severity, including case fatality [ 97 , 99 ]. Fortunately, however, mortality from DKA in elderly people have also declined dramatically during the past 10 years [ 100 ].…”
Section: Discussionmentioning
confidence: 99%